PERAN SEKOLAH RAMAH ANAK DALAM MENCEGAH DAN MENGATASI PERUNDUNGAN PADA ANAK USIA DINI - Haniya Haniya; Miftakhul Jannah; Yes Matheus Lasarus Malaikosa (CV. ADIBA AISHA AMIRA, 2024)
Childhood is a critical period in human development, where various aspects such as information reception, intelligence development, talent nurturing, and the instillation of moral values significantly influence future character and personality formation. However, bullying is a serious issue that threatens children's physical and psychological development. The child-friendly school program is a holistic and effective strategy to create a safe, inclusive, and supportive learning environment for all students, as well as to prevent and address bullying. This study employs a literature review method to explore the roles of principals, teachers, parents, and external parties in implementing the child-friendly school program. Principals act as leaders and main drivers in policy formulation and monitoring, teachers play roles in implementing an inclusive curriculum and providing emotional support to students, parents are involved in collaboration and monitoring at home, and external parties provide resources and policy advocacy. Strong collaboration among all these parties is essential to create a safe and supportive environment, allowing children to develop optimally.